Decreased risk of HIV‐associated TB during antiretroviral therapy expansion in rural Eswatini from 2009 to 2016: a cohort and population‐based analysis. Issue 9 (7th August 2019) - Kerschberger, Bernhard; Schomaker, Michael; Telnov, Alex; Vambe, Debrah; Kisyeri, Nicholas; Sikhondze, Welile; Pasipamire, Lorraine; Ngwenya, Siphiwe Mavis; Rusch, Barbara; Ciglenecki, Iza; Boulle, Andrew
Abstract: Objectives: This paper assesses patient‐ and population‐level trends in TB notifications during rapid expansion of antiretroviral therapy in Eswatini which has an extremely high incidence of both TB and HIV. Methods: Patient‐ and population‐level predictors and rates of HIV‐associated TB were examined in the Shiselweni region in Eswatini from 2009 to 2016. Annual population‐level denominators obtained from projected census data and prevalence estimates obtained from population‐based surveys were combined with individual‐level TB treatment data. Patient‐ and population‐level predictors of HIV‐associated TB were assessed with multivariate logistic and multivariate negative binomial regression models. Results: Of 11 328 TB cases, 71.4% were HIV co‐infected and 51.8% were women. TB notifications decreased fivefold between 2009 and 2016, from 1341 to 269 cases per 100 000 person‐years. The decline was sixfold in PLHIV vs. threefold in the HIV‐negative population. Main patient‐level predictors of HIV‐associated TB were recurrent TB treatment (adjusted odds ratio [aOR] 1.40, 95% confidence interval [CI]: 1.19–1.65), negative (aOR 1.31, 1.15–1.49) and missing (aOR 1.30, 1.11–1.53) bacteriological status and diagnosis at secondary healthcare level (aOR 1.18, 1.06–1.33). Compared with 2009, the probability of TB decreased for all years from 2011 (aOR 0.69, 0.58–0.83) to 2016 (aOR 0.54, 0.43–0.69). The most pronounced population‐level predictor of TB was HIV‐positive status (adjusted incidence risk ratio 19.47, 14.89–25.46). Conclusions: This high HIV‐TB prevalence setting experienced a rapid decline in TB notifications, most pronounced in PLHIV. Achievements in HIV‐TB programming were likely contributing factors. Abstract : Objectifs: Ce document évalue les tendances des notifications de la tuberculose (TB) à l'échelle des patients et de la population lors de l'expansion rapide du traitement antirétroviral à Eswatini, où l'incidence de la TB et du VIH est extrêmement élevée. Méthodes: Les prédicteurs et les taux de TB associée au VIH à l'échelle des patients et de la population ont été examinés dans la région de Shiselweni à Eswatini de 2009 à 2016. Les dénominateurs annuels à l'échelle de la population obtenus à partir des données de recensement projetées et des estimations de la prévalence obtenues à partir d'enquêtes de population ont été combinés avec des données de traitement de la TB à l'échelle individuel. Les prédicteurs de la TB associée au VIH à l'échelle du patient et de la population ont été évalués à l'aide de modèles de régression logistique multivariée et binomiale négative multivariée. Résultats: Sur 11.328 cas de TB, 71, 4% étaient coinfectés par le VIH et 51, 8% étaient des femmes. Les notifications de TB ont été réduites de 5, 0 fois entre 2009 et 2016, passant de 1.341 à 269 cas par 100.000 personnes‐années. Le déclin était de 6, 0 fois chez les PVVIH contre 3, 0 fois dans la population négative pour le VIH. Les principaux prédicteurs de la TB associée au VIH à l'échelle des patients étaient les traitements antituberculeux récurrents (rapport de cotes ajusté [aOR] 1, 40; intervalle de confiance à 95% [IC]: 1, 19 à 1, 65), un statut bactériologique négatif (aOR: 1, 31; 1, 15 à 1, 49) et manquant (aOR: 1, 30; 1, 11 à 1, 53) et le diagnostic au niveau des soins de santé secondaires (AOR 1, 18; 1, 06 à 1, 33). Par rapport à 2009, la probabilité de contracter la TB a diminué pour toutes les années, de 2011 (aOR: 0, 69; 0, 58 à 0, 83) à 2016 (aOR: 0, 5; 0, 43 à 0, 69). Le prédicteur le plus prononcé de la TB à l'échelle de la population était le statut VIH‐positif (rapport de risque d'incidence ajusté: 19, 47; 14, 89 à 25, 46). Conclusions: Ce contexte de prévalence élevée de la TB‐VIH a connu un déclin rapide du nombre de notifications de TB, plus prononcé chez les PVVIH. Les réalisations dans la programmation VIH‐TB étaient probablement des facteurs contributifs.